2019
DOI: 10.1111/jne.12779
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2: Its perspectives in brain pathology and possible roles in cognition

Abstract: Lipocalin‐2 (LCN2) has been known to play an important role in pathological conditions, specifically in response to inflammation, infection and injury to cells. Recently, several research teams have been interested in investigating its association with cognition during the progression of pathology. Previous studies have demonstrated that LCN2 is not correlated with cognitive function under normal physiological conditions, although LCN2 has been negatively associated with cognition and some neuropathologies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…In the CNS system, lipocalin-2 knockout mice with cerebral ischemia have been found to have smaller infarct volumes and better neurological functions, but the unexpected activation of astrocytes was not observed [ 83 ]. Recently, lipocalin-2 has been demonstrated to play a crucial role in pathological conditions, especially in pathological progression associated with cognition [ 84 , 85 ]. Elevated ItI It has been reported that lipocalin-2 is upregulated in a mouse’s hippocampus under psychological stress and modulates stress-induced neuronal excitability and anxious behavior [ 86 ], which has also been considered as a potential biomarker in Alzheimer’s disease and other aging-related cognitive decline [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS system, lipocalin-2 knockout mice with cerebral ischemia have been found to have smaller infarct volumes and better neurological functions, but the unexpected activation of astrocytes was not observed [ 83 ]. Recently, lipocalin-2 has been demonstrated to play a crucial role in pathological conditions, especially in pathological progression associated with cognition [ 84 , 85 ]. Elevated ItI It has been reported that lipocalin-2 is upregulated in a mouse’s hippocampus under psychological stress and modulates stress-induced neuronal excitability and anxious behavior [ 86 ], which has also been considered as a potential biomarker in Alzheimer’s disease and other aging-related cognitive decline [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, since lipocalin constitutes a marker of inflammation not necessarily associated with infection [ 48 ], our results highlight the importance of describing the inflammatory profile of OCD patients, given this might be of relevance for the understanding of the disorder in patients other than those evidencing OCS in the context of prior history of infection. Previous studies have demonstrated how other immune abnormalities might be related to glutamatergic dysfunction within the CSTC circuit, the main pathway associated with OCD development [ 16 , 49 ].…”
Section: Discussionmentioning
confidence: 98%
“…Most notably, LCN2-KO animals did not exhibit impairments in exploratory behavior or motor coordination nor showed deficits in the sucrose-preference, object recognition and object placement tests compared to control animals [ 45 ], which is in line with other reports where both LCN2 deficient and wild type mice exhibited a similar behavioral phenotype in response to liposaccharide injection [ 46 ]. Thus, it seems plausible to admit lipocalin may play different roles according to the physiology or pathological conditions [ 47 , 48 ] and further studies are needed to better understand its role in mediating disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lipocalin 2 has been reported to be released by injured neurons as a “help-me” distress signal that activates the astrocytes into potentially pro-recovery phenotypes [ 60 ]. Recently, lipocalin 2 has been shown to play an important role in pathological conditions, specifically its association with cognition during the progression of pathology [ 61 ]. Importantly, lipocalin 2 has previously been found to be upregulated in the hippocampus following psychological stress and regulates stress-induced neuronal excitability and anxious behavior [ 62 ], which has been considered as a potential biomarker in aging-related cognitive decline [ 63 ].…”
Section: Discussionmentioning
confidence: 99%